2021
DOI: 10.1001/jamanetworkopen.2021.33090
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Risk Among Patients With COVID-19 Prescribed Selective Serotonin Reuptake Inhibitor Antidepressants

Abstract: IMPORTANCE Antidepressant use may be associated with reduced levels of several proinflammatory cytokines suggested to be involved with the development of severe An association between the use of selective serotonin reuptake inhibitors (SSRIs)-specifically fluoxetine hydrochloride and fluvoxamine maleate-with decreased mortality among patients with COVID-19 has been reported in recent studies; however, these studies had limited power due to their small size. OBJECTIVETo investigate the association of SSRIs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
156
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(164 citation statements)
references
References 35 publications
6
156
0
2
Order By: Relevance
“…A recently published large retrospective study from the University of California, San Francisco, and Stanford University (UCSF/Stanford) suggests that SSRIs may be associated with decreased mortality from COVID [ 37 ]. This evaluation of in excess of 80,000 patients found that reduced mortality was confined to those taking fluvoxamine and fluoxetine.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published large retrospective study from the University of California, San Francisco, and Stanford University (UCSF/Stanford) suggests that SSRIs may be associated with decreased mortality from COVID [ 37 ]. This evaluation of in excess of 80,000 patients found that reduced mortality was confined to those taking fluvoxamine and fluoxetine.…”
Section: Discussionmentioning
confidence: 99%
“…From the treatment perspective, a multicenter, retrospective, observational study on hospitalized patients with COVID-19 has indicated a reduced risk of intubation or death in patients taking antidepressants, particularly fluoxetine (Hoertel et al 2021b). Similarly, a large retrospective cohort study observed reduced mortality in patients treated with fluoxetine or fluvoxamine compared to matched patients not treated with these or any other SSRIs (Oskotsky et al 2021). Two further randomized placebo-controlled trials and a prospective real-world study support the observation of a lower risk of clinical deterioration over two weeks of treatment with fluvoxamine (Lenze et al 2020;Reis et al 2022;Seftel and Boulware 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The increased mortality rates among COVID 19 patients increased the demand to check for drugs that may reduce the high risk of death especially in advanced age [35, 36] . In their large multicenter retrospective observational cohort study, Oskotsky et al indicated the effectiveness of SSRIs, specifically fluoxetine and fluoxetine or fluvoxamine, in reducing the mortality rates among the groups that used this category of antidepressants compared to the control group [37] . In our review, we found that there was no significant difference in the ITT mortality rates between fluvoxamine group and placebo or SC (RR = 0.66; 95% CI: 0.36 - 1.21).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this can give the preference to the use of fluoxetine over fluvoxamine in the reduction of mortality among COVID-19 patients. We can also infer from this the superiority of fluoxetine and fluvoxamine over the other SSRIs [37, 38] .…”
Section: Discussionmentioning
confidence: 99%